Wrongdoing or improper conduct in an a organisation: employee's duty to 'blow the whistle' from an Islamic perspective - Ali Mohamed, Ashgar Ali (LexisNexis, 2015)
The Whistleblower Protection Act 2010, was enacted by the Malaysian Parliament in June 2010 in an attempt to supress corruption and to protect individuals in an organisation who attempts to expose an alleged dishonesty or illegal activity that violates the existing laws, among others. The Act encourages and facilitates the anonymous whistleblowing of wrongdoing or improper conduct in the public and private sector. The Act provides, inter alia, protection of the whistleblower against the disclosure of confidential information, immunity from civil and criminal action and protection against retaliatory action or reprisals. The whistleblower protection however is dependent on the fulfilment of certain requirements namely, that the disclosure must be done in good faith with a reasonable belief of the improper conduct to the designated enforcement agencies specified by the Act. However, no protection is available when the complaint or communication was made to other than the designated enforcement agency. Further, the disclosure must not be prohibited or violates the existing written laws such as the disclosure of customer profiles in breach of the Financial Services Act 2013 or the dissemination of information classified as an official secret under the Official Secrets Act 1972, among others. Having said the above, this article explores the whistleblowing from the Islamic perspective in the context of employment relationship.